Vergleich von deutschen Arbeitsmarktregionen - Hans-Friedrich Eckey; Barbara Schwengler; Matthias Türck (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
There are two delineations of German labour market regions. On the one hand the 'Gemeinschaftsaufgabe Verbesserung der regionalen Wirtschaftsstruktur' uses labour market regions for business development programs. Their demarcation is based on 270 functional areas after a modification for the regions of Berlin/Brandenburg. On the other hand there is a demarcation of Eckey/Kosfeld/Türck (2006). Their labour market regions are more spacious compared to the regions of the 'Gemeinschaftsaufgabe', because their data set covers 150 spatial units. Both definitions are based on commuter flows, and the regions are quite independent economic areas. Labour market regions are more suitable for labour economic analyses than administrative units such as Kreise, federal states, NUTS-2-regions etc. The articles uses the example Berlin/Brandenburg and points out, how both demarcations are calculated. In addition we draw a comparison of both delineations.
Keywords: C21; J40; R12; R58; 330; Gemeinschaftsaufgabe Regionale Wirtschaftsförderung; Fördergebiet; Arbeitsmarktregion; Regionalgliederung; Berlin-Brandenburg; Bundesrepublik Deutschland; Regionaler Arbeitsmarkt; Relevanter Markt; Vergleich; Deutschland; Brandenburg; Berlin (Region)